Testemunho e responsabilidade: o dizer de Semprún sob a ética de Lévinas - FIGUEIREDO, Elielson de Souza (Universidade Federal do Pará, 2021)
This doctoral thesis concentrates efforts to bring philosophical thinking closer to Emmanuel Lévinas (Kaunas, Lithuania, 1906) of the theoretical categories of analysis of the Witness Literature produced from the surviving Shoah. With order to prove that the philosophy of otherness of Lévinas offers a valuable theoretical set for the studies about the Testimony as a point of intersection between Memory, Fiction and History, the thesis focuses in the autofictional writing of Jorge Semprún (Madrid, Spain, 1923), particularly about the novels A grande Viagem and A escrita ou a vida.The central argument defended here states that the self-production produced by Semprún can be understood in the conceptual key of what Lévinas calls Responsibility, that is, as the survivor's response to the unjustified suffering under which millions of people imprisoned and murdered in the camps suffered and died forced labor and extermination, maintained during the German nazi regime. Starting from the hypothesis that testimony is to assume the ethical task of resisting the banalization of murder, the thesis investigates a small conceptual group that, along the philosophical thought of Lévinas, is linked to responsibility: election, convocation, face, passivity and ethical subjectivity form the basis of argument defended here. Through alternate quotes and comments that allow us to read the criticism with the Testimony through the reflections of Lévinas, besides allowing us to read the philosophy of otherness through the words of figures like Seligmann-Silva, Gagnebin, Agamben, Rosani Umbach and Tania Sarmento - Pantoja, this thesis intends to create an important theoretical discussion for this same critic of this philosophy. About Jorge Semprún, his work of autofiction is read here in the theoretical key of Tell and taken as an ethical gesture of desubjectivation insofar as in re-elaborating his experiences in the forced labor camp of Buchenwald, where he was a political prisoner between 1943 and 1945, the writer uses the artifice to fictionally recreate facts and characters of his survival during the prison, in order to produce an ambiguity between history, autobiography and fiction. Thus, supported by theoreticians such as Philippe Lejeune, Ángel Loureiro, Leonor Arfuch and Manuel Alberca, this thesis demonstrates how Semprun's autofiction intends the possibilities of language exposing the conscience or ethical subjectivity of the survivor who, even in the face of the limits imposed on the task of Tell the excess of traumatic events, does not shy away from exposing the insufficiency of his writing and thus attends to the Responsibility of the convocation to witness.